Product-safety considerations in allogeneic chimeric antigen-receptor T-cell process flows. (December 2022) - Dransart, Bryan; Dehghani, Houman; Moore, Alison
Abstract : Allogeneic chimeric antigen-receptor T-cell process flows comprise large-scale primary cultures incorporating traditional biologics processing steps such as cell expansion, with novel processing steps such as electroporation. In addition, these process flows begin with donor-derived peripheral blood mononuclear cells and generate single batches of product, which may be used to treat hundreds of patients. The corresponding unit operation-process safety considerations are individually diverse, and in combination are currently unique and rapidly evolving. The use of available regulations and the principles of quality by design are useful in designing appropriate control strategies into the process during development to ensure process safety. Highlights: Allogeneic processes present new opportunities for building safety and control into the manufacturing process. Screening and safety testing for adventitious agents are needed for final release of all critical starting materials and components. Viral-vector production processes should utilize cell substrates that have been tested and characterized, process raw materials that are chemically defined and ideally animal-component free, and free from detectable adventitious agents. Ex-vivo gene editing outcomes should be monitored and assessed for potential off-target edits and chromosomal translocations. A comprehensive process control matrix can be developed including starting materials, raw materials, process and product impurities, microbial, and adventitious agent control.